Pemberian Domperidon Oral dalam Mengatasi Muntah pada Pasien Diare Cair Akut Anak Dibandingkan Dengan Plasebo - , Bibang Rivandiari Syamsi, dr. Muchamad Juffrie, SpA(K), PhD ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: Acute watery diarrhea is common cause of morbidity and mortality in children. Vomit also complicates the rehydration management, although antiemetics are not recommended within standard medical protocol. Domperidone is common prescribed antiemetics for diarrhea and no adverse effects reported in such cases. However, adequate evidence to supports that domperidone benefits in reducing vomiting secondary to acute watery diarrhea in children. Objective: This study aimed to measure the benefits of domperidone compared with placebo in reducing vomit secondary to acute watery diarrhea in children. Methods: We conducted a randomized double-blind controlled trial in Emergency Room and Pediatric Clinic at Dr Sardjito Hospital, Wates Distric Hospital, and Soeradji Tirtonegoro Hospital between August to September 2007. We recruited infants and children aged 2 mo to 6 years with vomit secondary to acute watery diarrhea. Subjects were randomized to receive either domperidon or placebo. The outcomes of the study were occurrence of vomiting, vomit frequency, diarrhea frequency during rehydration, and diarrhea duration. Result: Domperidone decreased overall vomit proportion (overall relative risk reduction 0.89, 95% CI 0.7 to 0.95, NNT 1) and decreased overall vomit frequency during rehydration (overall episode reduction -3.26 , 95% CI -3.65 to -2.86). There was no significant difference in diarrhea duration and frequency between groups and no side effects were reported. Conclusion: Domperidone significantly decreases proportion and frequency of vomit during rehydration without increasing the frequency and duriation of diarrhea. Domperidone is also safe for 2 months to 6 year old children.